Akka in action - Sancho-Abraham, Francisco Lopez; Bakker, Robertus; Williams, Rob; Roestenburg, Raymond (Manning Publications, 2023)
Akka solves the big problems of distributed systems, from multithreading and concurrency to scalability and failure. Learn how to use it effectively. In Akka in Action, Second Edition you will learn how to: Create basic programs with Akka Typed Work with clusters to build robust, fault-tolerant programs Use Akka with Kubernetes Build microservices with Akka Create and maintain distributed state with strong consistency guarantees Employ actor-based concurrency and parallelism Test Akka software Akka in Action, Second Edition teaches you to use Akka Typed to solve common problems of distributed systems. You'll learn how to bring together all of Akka's moving parts to design and implement highly scalable and maintainable software. Extensively revised by Akka contributor Francisco L©đpez-Sancho Abraham, this new edition demonstrates Akka's complex concepts through engaging hands-on examples. Discover the power of the Actor Model, how Akka works with Kubernetes, and how to utilize Akka modules to create microservices that are reliable and fault tolerant. About the Technology For large software systems, the action is in the "-ilities." Scalability. Reliability. Maintainability. Capability. Akka, toolkit for building distributed message-driven applications, delivers on the "ilities." And recent innovations, including Akka Typed, ensure that this amazing platform will remain the best way to build and deploy distributed Java and Scala applications for years to come. About the Book Akka in Action, Second Edition is your guide to building message-centric distributed applications systems. This new edition covers all features of Akka, including Akka Typed. You'll learn to create microservices using Akka's powerful suite of tools, Akka Sharding, Persistence, Streams, Persistence Query, Projections, and gRPC. Practical examples taken directly from industry guide you through clustering, deploying to Kubernetes, and taking full advantage of Akka's Actors-based approach to concurrency. What's Inside Work with clusters to build robust, fault-tolerant programs Maintain distributed systems with strong consistency guarantees Utilize concurrency and parallelism Test Akka software About the Reader For readers comfortable with Java and Scala. About the Authors Francisco Lopez Sancho-Abraham is a senior consultant at Lightbend, and a principal engineer on the Akka Team. Raymond Roestenburg, Rob Bakker, and Rob Williams are the authors of the first edition of Akka in Action. Quotes Akka in Action is the best source for a deep yet practical and hands-on introduction to Akka. In it, Francisco discusses everything from the foundational distributed systems stuff to how to integrate it with the more recent high-level modules like Alpakka and Akka Streams. Highly recommended. - Jonas Bon©♭r, Lightbend All you need to start with Akka and the Actor Model. - Rares Tausancea, ING A gem that few books can match when it comes to Actors, CQRS, and Event Sourcing. For Scala and Java developers, it's an essential read. - Sebastian Harko, IBM Delivers a powerful combination of easy-to-follow lessons on the Akka ecosystem and well-timed discussions on important topics in modern computing. - John Ackley, Carnegie Learning.
Online resource; title from title details screen (O'Reilly, viewed January 31, 2024)
Keywords: Akka; Internet programming; Programmation Internet; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet